Foreign ownership restrictions and stock prices in the Thai capital market - Bailey, Warren; Jagtiani, Julapa (Journal of Financial Economics, 1994)
We study the effects of barriers to capital flows using data from the Stock Exchange of Thailand, which segments local and foreign trading of securities that have reached foreign ownership limits. Cross-sectional differences between local and foreign prices are correlated with proxies for the severity of foreign ownership limits, liquidity, and information availability. Time-series variability in the spread between local and foreign returns is consistent with differences in risk exposures and expected risk premiums, suggesting effective capital market segmentation. The results have numerous implications for portfolio and direct investment activity in developing countries.